Pocket guide to gastrointestinai drugs - Wolfe, M. Michael; Lowe, Robert C., 1966- (Chichester, West Sussex : John Wiley & Sons, 2014)
"Learn all you need to know about gastrointestinal drugs and their clinical use with this one-stop, rapid reference pocket guide. Brought to you by many of the world's leading GI drug experts, Pocket Guide to Gastrointestinal Drugs provides comprehensive guidance to the pharmacological properties of drugs used to treat gastrointestinal conditions, including mechanisms of action, appropriate administration, and potential adverse effects associated with their use. Organized by class of drug and ranging from PPIs to immunosupressants, each chapter first examines the specific agents within that class and then their appropriate and judicious use across a range of specific GI disorders. Key features include: - Introduction of drug class, - Basic pharmacology, including mechanism of action, bioavailability, metabolism, interactions, adverse effects, toxicity, and special considerations, - Dosing information for each GI condition and on- and off-label use, - Consistent use of both generic and trade names throughout, - Specific reference to drug use in pediatric patients and during pregnancy. Perfect for quick consultation on the wards and in the office, Pocket Guide to Gastrointestinal Drugs is the ideal tool for all those managing patients with GI conditions, including gastroenterologists, GI trainees, emergency physicians, GI specialist nurses, primary care physicians and residents, intensivists and pharmacists"--Provided by publisher.
Clinical effectivenessNucleoside analogs; Nucleotide analogs; Summary; Recommended reading; Chapter 11: Ursodeoxycholic acid, chelating agents, and zinc in the treatment of metabolic liver diseases; Ursodeoxycholic acid; Treatment of copper overload; Recommended reading; Chapter 12: Agents for the treatment of portal hypertension; Introduction; Nonselective beta-blockers (NSBB); Nitrates; Vasopressin analogs; Somatostatin analog; Midodrine; Albumin; Loop diuretics; Aldosterone antagonist; Aquaretics; Disaccharides; Antibiotics; Recommended reading; Chapter 13: Pancreatic enzymes; Introduction.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Gastrointestinal agents -- Handbooks, manuals, etc; Gastrointestinal Agents -- therapeutic use; Gastrointestinal Agents -- pharmacology; Gastrointestinal Diseases -- drug therapy; Gastrointestinal agents -- Pharmacology -- Handbooks; Gastrointestinal agents -- Therapeutic use -- Handbooks; Gastrointestinal diseases -- Drug therapy -- Handbooks; MEDICAL -- Pharmacology; Gastrointestinal agents; Handbooks; Electronic books; Handbooks and manuals